2017
DOI: 10.20344/amp.8235
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes: Socioeconomic Inequalities in the Portuguese Population in 2014

Abstract: Diabetes is a major public health problem and it is related to socioeconomic factors. The aim of this study is to describe socioeconomic inequalities in the distribution of diabetes in the population with 25 years or more, resident in Portugal in 2014. Material and Methods:Data from the Health National Survey 2014 was analysed, n = 16 786. We estimated the prevalence of diabetes in the population and stratified by socioeconomic variables namely educational level and income. The extent of socioeconomic inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Middle-aged and elderly women have a significantly greater likelihood of diabetes than men according to our results which is again in agreement with the previous studies [11, 12, 15]; this result may be related to the menopause. Older people were found to have a higher prevalence of diabetes, as reported by most previous studies in this field [3, 5, 1115, 27, 35]. Marriage is protective of health in general, and this is especially true among older couples [36].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Middle-aged and elderly women have a significantly greater likelihood of diabetes than men according to our results which is again in agreement with the previous studies [11, 12, 15]; this result may be related to the menopause. Older people were found to have a higher prevalence of diabetes, as reported by most previous studies in this field [3, 5, 1115, 27, 35]. Marriage is protective of health in general, and this is especially true among older couples [36].…”
Section: Discussionmentioning
confidence: 71%
“…Diabetes-related inequality is dynamic and dependent on cultural and societal development [24]. Moradi et al [25] reported that diabetes inequality shifted from poor people to the rich in Iran, while other studies found an inverse relationship between socioeconomic inequality and the prevalence of diabetes in Germany and Portugal [26, 27]. Biswas et al [28] revealed a disproportionate concentration of diabetes among the richest urban and the poorest rural populations in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing reliable sources and channels about diabetes: Studies emphasized that information sources used by diabetic patients should be among the most reliable sources of health information. [ 34 35 36 37 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…Develop a purposeful strategy in providing knowledge and skills tailored to the HL of individuals: The results of research in the world suggested that providing HL should be customized for different groups in society. [ 6 11 22 23 24 25 26 30 34 35 37 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation